Kontekstualitas Dalam Implementasi Good Governance: Studi Multi-Kasus Inovasi Dan Tantangan Di Kelurahan Kota Padang - Citra Zefanya Hesi; Fadillah Harmi; Khairunnisa Nabilah; Salma Melco Indriani; Jumiati; Boni Saputra (CV. ITTC INDONESIA, 2025)
The implementation of good governance principles at the sub-district (kelurahan) level plays a crucial role in promoting transparent, accountable, and participatory local administration. This study aims to analyze the implementation strategies of good governance in several sub-districts in Padang City using a qualitative approach, through case studies and literature analysis. Five prior research articles were reviewed to identify patterns, obstacles, and best practices in applying these principles. The findings reveal that digital innovations, such as the e-Kelurahan system and SIRANCAK, have contributed to improving transparency and efficiency. However, limitations remain, particularly in community digital literacy, lack of training, and low public participation. Additionally, issues related to accountability and service ethics—such as informal practices and lack of public oversight—indicate that not all principles are fully implemented. The study emphasizes that good governance strategies must be context-sensitive and adaptive to local social conditions. Synergy between technology, ethical values, and community empowerment is essential to realizing effective and inclusive local governance.